2020
DOI: 10.1002/ajh.25937
|View full text |Cite
|
Sign up to set email alerts
|

Individual red blood cell fetal hemoglobin quantification allows to determine protective thresholds in sickle cell disease

Abstract: Polymerization of the sickle hemoglobin (HbS) is a key determinant of sickle cell disease (SCD), an inherited blood disorder. Fetal hemoglobin (HbF) is a major modulator of the disease severity by both decreasing HbS intracellular concentration and inhibiting its polymerization. However, heterocellular distribution of HbF is common in SCD. For HbS polymerization inhibition, the hypothesis of an "HbF per red blood cell (HbF/RBC) threshold" requires accurate measurement of HbF in individual RBC. To date, HbF det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…These studies and others paint an increasing better understanding of the molecular regulation of hemoglobin switching and genetic heterogeneity in SCD and other hemoglobin variant disorders, such as thalassemia. The early studies with LDT versions of the HbF RBC assays make clear that patients may respond in either a homocellular or heterocellular HbF distribution fashion among RBCs, as reaffirmed by the current study by Hebert et al , 1 the important parameter correlating with therapeutic response is the population size of RBCs having a threshold approximating >4 pg HbF per cell, seemingly where sufficient intercalating HbF prevents the polymerizing sickling phenomenon in SCD. It remains to be determined if the critical threshold for sickling prevention is a specific level of HbF in the cell or if merely achieving a certain proportion of HbF of the total cellular hemoglobin content is sufficient to predict sickling phenotype remains to be determined.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…These studies and others paint an increasing better understanding of the molecular regulation of hemoglobin switching and genetic heterogeneity in SCD and other hemoglobin variant disorders, such as thalassemia. The early studies with LDT versions of the HbF RBC assays make clear that patients may respond in either a homocellular or heterocellular HbF distribution fashion among RBCs, as reaffirmed by the current study by Hebert et al , 1 the important parameter correlating with therapeutic response is the population size of RBCs having a threshold approximating >4 pg HbF per cell, seemingly where sufficient intercalating HbF prevents the polymerizing sickling phenomenon in SCD. It remains to be determined if the critical threshold for sickling prevention is a specific level of HbF in the cell or if merely achieving a certain proportion of HbF of the total cellular hemoglobin content is sufficient to predict sickling phenotype remains to be determined.…”
supporting
confidence: 79%
“…The work of Hebert, Rakotoson et al in this issue of the American Journal of Hematology 1 points to evolving in vitro Diagnostics (IVD) testing of red blood cell (RBC) hemoglobin levels, now poised for a clear role in the personalized care and therapeutic management of sickle cell disease (SCD) patients, long known to be a genetically and clinically heterogenous patient population 2‐4 . The performance and validation studies detailed in this article and supplement material describe a laboratory developed flow cytometric test (LDT) capable of providing sufficient precision to measure threshold levels of hemoglobin F (HbF) in a clinically meaningful way.…”
mentioning
confidence: 97%
“…In the present study, we describe the utility of flow cytometric F‐cell analysis and demonstrate sustained and near‐pancellular or pancellular distribution of HbF in this cohort. We show that hydroxyurea, when given in this manner, can achieve or exceed the goals defined for ‘curative therapies’ for SCA 12–14 …”
Section: Introductionmentioning
confidence: 85%
“…Several recent publications have suggested that curative therapies should aim to achieve HbF >30%, F‐cells >70% and >4–10 pg F/F‐cell 12–14 . We have demonstrated that early initiation of hydroxyurea using individualised, pharmacokinetics (PK)‐guided dosing results in robust and sustained HbF levels beyond 30–40% for most adherent patients 15,16 .…”
Section: Introductionmentioning
confidence: 86%
“…From a circulatory physiology perspective these include the time dependence of oxygen pressures for humans as red cells enter and exit tissues, the transit times in humans for red cells through the smallest vessels where sickled cells could become stuck, and measurements similar to those of Ferrone and coworkers (50,81) but which also take into account adhesion to the capillary endothelium. For more accurate calculations of sickling, information on composition heterogeneity is required, especially for the distribution of fetal hemoglobin at each total intracellular hemoglobin concentration (102). Also needed are additional measurements on purified solutions of mixtures of HbS with HbF and HbA, including delay times and solubilities as a function of fractional saturation under physiological conditions, to resolve the discrepancies in copolymerization probabilities from solubility and polymer phase composition measurements (54).…”
Section: Discussionmentioning
confidence: 99%